Food Prices and Poverty - Headey, Derek D. (World Bank, Washington, DC, 2016)
Do higher food prices help or hinder poverty reduction? Despite much debate, existing research has almost solely relied on simulation models to address this question. In this paper World Bank poverty estimates are used to systematically test the relationship between changes in poverty and exogenous changes in real domestic food prices. The paper uncovers indicative evidence that increases in food prices are associated with reductions in poverty, not increases. A likely empirical explanation is the relatively strong agricultural supply and wage responses to food price increases, and the fact that the majority of the world's poor still heavily rely on agriculture or agriculture-related activities to earn a living.